Common Carotid Artery Diameter and Risk of Cardiovascular Events and Mortality: Pooled Analyses of Four Cohort Studies. Issue 1 (July 2018) - Sedaghat, Sanaz; van Sloten, Thomas T.; Laurent, Stéphane; London, Gérard M.; Pannier, Bruno; Kavousi, Maryam; Mattace-Raso, Francesco; Franco, Oscar H.; Boutouyrie, Pierre; Ikram, M. Arfan; Stehouwer, Coen D.A.
Abstract : Carotid arterial diameter enlargement is a manifestation of arterial remodeling and may be a risk factor for cardiovascular disease (CVD). We evaluated the association between carotid artery diameter and risk of stroke, coronary heart disease, CVD, and all-cause mortality and explored whether the associations could be explained by processes involved in arterial remodeling, that is, blood pressure–related media thickening, arterial stiffness, arterial wall stress, and atherosclerosis. We included 4887 participants (mean age 67±9 years; 54% women) from 4 cohort studies: Rotterdam Study, NEPHROTEST, Hoorn Study, and a study by Blacher et al. Common carotid artery properties were measured using echotracking. Incident cases were recorded based on medical records. We used Cox proportional hazard models adjusting for cardiovascular risk factors and estimates of processes underlying arterial remodeling. During follow-up (mean, 11 years), 379 (8%) individuals had a stroke, 516 had a (11%) coronary heart disease, 807 had a (17%) CVD, and 1486 (30%) had died. After adjustment for cardiovascular risk factors, individuals in the highest tertile of carotid diameter (diameter >8 mm) compared with those in the lowest tertile (diameter <7 mm) had a higher incidence of stroke (hazard ratio, 1.5; 95% confidence interval, 1.1–2.0). From all estimates of processes underlying arterial remodeling, adjustment for carotid intima-media thickness attenuated this association (hazard ratio after adjustment for intima-media thickness, 1.2; 95% confidence interval, 0.9–1.6). Larger carotid diameter was associated with risk of CVD and mortality but not clearly with coronary heart disease risk. We showed that a larger carotid diameter is associated with incident stroke, CVD, and mortality. Carotid intima-media thickness, a measure of blood pressure–related media thickening, partially explained the association with stroke incidence. Abstract : Supplemental Digital Content is available in the text.